A hierarchical, stretchable and stiff fibrous biotemplate engineered using stagger-electrospinning for augmentation of rotator cuff tendon-healing. Issue 6 (16th December 2014) - Zhao, Song; Zhao, Xin; Dong, Shikui; Yu, Jia; Pan, Guoqing; Zhang, Yang; Zhao, Jinzhong; Cui, Wenguo
Abstract : Engineering hierarchical, stretchable and stiff fibrous biotemplate using stagger-electrospinning for the augmentation of rotator cuff tendon-healing. Abstract : The regeneration of fibrocartilage at the tendon–bone insertion site in rotator cuff tears (RCTs) is challenging due to the complexity of its composition and mechanical properties. In this study, hierarchical, stretchable and stiff fibrous scaffolds composed of microfibers of poly(ε-caprolactone) (PCL) and nanofibers of chitosan (CS) were fabricated using stagger-electrospinning for the augmentation of RCT-healing. It was found that the composite PCL-CS scaffolds had significantly improved strength and failure strain compared to the control CS scaffolds and increased stiffness compared to the control PCL scaffolds. These scaffolds also showed enhanced hydrophilicity, water absorption and a faster degradation rate compared to the PCL scaffolds. Moreover, they demonstrated better fibroblast attachment and proliferation compared to the PCL scaffolds. Radiological and histological analysis revealed that the PCL-CS scaffolds enhanced new bone formation (mineralization) and collagen and glycosaminoglycan expression (major components of extracellular matrix) compared to the PCL scaffolds. Furthermore, the torn tissues at the tendon–bone insertion site regenerated with the PCL-CS scaffolds showed higher strength and failure strain as well as stiffness compared to those repaired using only the PCL scaffolds. The above mentioned results suggest that the hierarchical, stretchable and stiff fibrous scaffolds engineered using stagger-electrospinning have great potential for the augmentation of RCT-healing.